2013
DOI: 10.1007/s11845-013-0931-0
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood CD40–CD40L expression in human breast cancer

Abstract: The upregulated levels of co-stimulators CD40/CD40L on B cells and T cells may play an important role in the immune pathogenesis of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…In accordance, the expression levels of CD40/CD40L have also been found to be increased in breast cancer, displaying a positive relationship with pathological grade [55]. A recent study, showed that the production of TGF-β induced by the CD40-CD40L interaction resulted in enhanced immunosuppressive function of breast cancer cells, thereby contributing to tumor progression [55]. …”
Section: Discussionmentioning
confidence: 85%
“…In accordance, the expression levels of CD40/CD40L have also been found to be increased in breast cancer, displaying a positive relationship with pathological grade [55]. A recent study, showed that the production of TGF-β induced by the CD40-CD40L interaction resulted in enhanced immunosuppressive function of breast cancer cells, thereby contributing to tumor progression [55]. …”
Section: Discussionmentioning
confidence: 85%
“…The reason why post-CRT sCD40L levels are significantly reduced in High-R is not known, but it is known that, in addition to the immunomodulatory effects, the CD40 signaling pathway also plays an important role in proliferation, differentiation and apoptosis of cancer cells. Many tumor cells also express CD40 (29)(30)(31)(32), and evidence suggests that ligation of CD40 might promote either cell proliferation or apoptosis, depending on the intensity of CD40L signaling (33,34). Although we did not investigate the expression of CD40 in cancer cells, it can be speculated that sCD40L may induce antitumor effects, either through binding to immune cells, stimulating an antitumor immunity, or through the direct binding to cancer cells, inducing their apoptotic cell death; in both situations, sCD40L levels are reduced by consumption.…”
Section: D Venous Invasionmentioning
confidence: 99%
“…CD40L, which is a type II membrane-related glycoprotein and a member of the tumor necrosis factor (TNF) superfamily [22], is conducive to regulate the immune response and inhibit tumor growth. It produces direct growth-inhibiting effect through apoptosis in CD40L over-expressed malignant tumor cells (such as breast cancer) [23]. The correlation of ICGs expression level in both databases is positive and is showing an obvious aggregation effect, indicating a possibility of coordinated expression relationship between ICGs.…”
Section: Discussionmentioning
confidence: 95%